Strategi Amerika Serikat dalam Menghadapi Dominasi Logam Tanah Jarang Tiongkok - Allo, Kembang Lisu; Wicaksono, Arief; Fauzi, Muhammad Fahmi Basyhah (Journal of International and Local Studies, 2025)
China is one of the dominant actors in the global rare earth elements market. This dominance then created a situation of dependence on China's rare earth metals. This research aims to analyze the United States Government's strategy in dealing with China's dominance of rare earths in the global market. The author uses the theory of offensive neorealism by John Mearsheimer as a conceptual framework in an attempt to explain the strategy of the United States. The type of research used is qualitative research with data collection techniques through library research in the form of primary data such as the official website of the United States Government, reports of rare earth companies in the United States, China and Australia, as well as secondary data sourced from research institutions, think tanks, articles from scientific institutions and professional organizations. After the data was collected and analyzed, the authors concluded that the United States' efforts to reduce import dependence were carried out by taking strategic steps through Executive Order or Executice Order 13817 and the Defense Production Act (DPA) during the Donald J Trump Administration (2017-2021). The move is a way to balance forces in limiting China's widespread dominance of rare earth metals. This effort is the impact of the dynamics of the international system that is anarchy, where the big countries never stop competing and pursuing power. Keywords: Rare Earth Elements, China’s Dominance, United State Import Dependency, United State Strategy, Offensive Neorealism